Quantitative risk-benefit assessment of Portuguese fish and other seafood species consumption scenarios - Carvalho, Catarina (2022)
Portugal has high fish/seafood consumption, which may have both risks and benefits. This study aims to quantify the net health impact of hypothetical scenarios of fish/seafood consumption in the Portuguese population using a risk-benefit assessment methodology. Consumption data from the National Food, Nutrition and Physical Activity Survey 2015-2016 (n 5811) were used to estimate the mean exposure to methylmercury and EPA + DHA in the current and the alternative scenarios considered. Alternative scenarios (alt) were modelled using probabilistic approaches to reflect substitutions from the current consumption in the type of fish/seafood (alt1: excluding predatory fishes; alt2: including only methylmercury low-level fishes) or in the frequency of weekly fish/seafood consumption (alt3 to alt6: 1, 3, 5 or 7 times a week, replacing fish/seafood meals with meat or others). The overall health impact of these scenarios was quantified using disability-adjusted life years (DALY). In the Portuguese population, about 11 450 DALY could be prevented each year if the fish/seafood consumption increased to a daily basis. However, such a scenario would result in 1398 extra DALY considering the consumption by pregnant women and the respective risk on fetal neurodevelopment. Our findings support a recommendation to increase fish/seafood consumption up to 7 times/week. However, for pregnant women and children, special considerations must be proposed to avoid potential risks on fetal neurodevelopment due to methylmercury exposure.